2006
DOI: 10.1200/jco.2006.05.9592
|View full text |Cite
|
Sign up to set email alerts
|

Do Patients With Localized Prostate Cancer Treatment Really Want More Aggressive Treatment?

Abstract: Most patients with localized prostate cancer prefer the lower radiation dose. Our findings indicate that many patients attach more weight to specific quality-of-life aspects (eg, GI toxicity) than to improving survival. Treatment preferences of patients with localized prostate cancer can and should be involved in radiotherapy decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(40 citation statements)
references
References 27 publications
2
34
1
2
Order By: Relevance
“…[38][39][40]43 Four studies incorporated the DA into the physician visit. [30][31][32][33][34] Only 1 study reported data concerning the length of 38 In general, participants found DAs to be helpful and were satisfied with the content. Brink et al 41 and Holmes-Rovner et al 36 reported data concerning the clarity and usefulness of the DAs themselves.…”
Section: How Acceptable and Feasible Is The Use Of Das In Practice?mentioning
confidence: 99%
See 4 more Smart Citations
“…[38][39][40]43 Four studies incorporated the DA into the physician visit. [30][31][32][33][34] Only 1 study reported data concerning the length of 38 In general, participants found DAs to be helpful and were satisfied with the content. Brink et al 41 and Holmes-Rovner et al 36 reported data concerning the clarity and usefulness of the DAs themselves.…”
Section: How Acceptable and Feasible Is The Use Of Das In Practice?mentioning
confidence: 99%
“…38 van Tol-Geerdink et al tested a written DA within the context of an interview. 30,31,34 Treatment options discussed in the DAs varied. Six DAs discussed "watchful waiting," surgical options, and radiation therapy (external beam radiation or brachytherapy).…”
Section: Types Of Das and Control Interventionsmentioning
confidence: 99%
See 3 more Smart Citations